A systematic review of ergonomic risk factors associated with computer work-related musculoskeletal disorders in office workstations - Abdol Rahman, Mohd Nasrull; Mohamad, Siti Shafika (2016)
This review aims to give an overview of ergonomic risk factors associated with computer work-related musculoskeletal disorders in office workstations. Data from 1990 until 2015 was revised using electronic databases.The overview based on computer work, office risk factors,musculoskeletal disorders, working posture, office components and office environment.Epidemiologic studies show that physical exposure has a moderate and strong association with Computer Work-Related Musculoskeletal Disorders.Sixteen items of risk factors with significant associations with body part exposure outcomes were identified.Ergonomic risks factors involved awkward postures , repetitive movement, excessive force and office environment.This study describes recommended posture angles as well as appropriate distance between office workers and office equipment.